A multiple objective optimization based QFD approach for efficient resilient strategies to mitigate supply chain vulnerabilities: The case of garment industry of Bangladesh - Chowdhury, Md. Maruf Hossan; Quaddus, Mohammed (Pergamon Press, 2015)
With the upsurge of frequent disruptive events, organizations have become more vulnerable to the consequences of these disruptive events. As a result, the need for more resilient supply chain (SC) to mitigate the vulnerabilities has become paramount. Supply chain resilience (SCR) has been discussed in the literature and resilience index has been developed, but developing and selecting a portfolio of supply chain resilience capabilities in order to mitigate the vulnerabilities have not been studied. In this research we develop a 0-1 multi-objective optimization model based on QFD methodology. Our multi-objective method is interactive and interacts with the decision makers to choose the most satisfactory efficient portfolio of supply chain resilience strategies. We apply our methodology to three large ready-made garment (RMG) companies of Bangladesh. Results show that lack of materials (high dependence on imported materials), disruptions in utility supply, increased competition (and hence competitive pressure), impact of economic recession, and reputation loss are the top most vulnerabilities of Bangladesh RMG industry. The most preferred resilience strategies to mitigate the vulnerabilities are: back-up capacity, building relation with buyers and suppliers, quality control, skill and efficiency development, ICT adoption, demand forecasting, responsiveness to customers, and security system improvement. Theoretical and managerial implications of our study are included.